2008
DOI: 10.1021/bi801883v
|View full text |Cite
|
Sign up to set email alerts
|

Pseudoirreversible Inhibition of Prostate-Specific Membrane Antigen by Phosphoramidate Peptidomimetics

Abstract: The mode of inhibition for phosphoramidate peptidomimetic inhibitors of prostate-specific membrane antigen was determined by inhibition reversibility experiments. The results revealed that these inhibitors can be classified into three types: pseudoirreversible (compounds 1-3), moderately reversible (compounds 4-9), and rapidly reversible inhibitors (compounds 10 and 11). Representative compounds from each class were further evaluated for their ability to induce cellular internalization of PSMA. Results from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
103
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 75 publications
(116 citation statements)
references
References 20 publications
12
103
0
Order By: Relevance
“…The blockade experiment with 2-PMPA as a competing ligand led to a significant, but not complete, reduction in tumor uptake. This result might be attributable to the binding mechanism of 2-PMPA, as it has been reported to be a fast and reversible inhibitor (21). Given the high internalization ratio of 18 F-PSMA-1007, only a small fraction of the ligand needs to be bound to be internalized-even in the presence of the competitorand thus might result in significant uptake into the tumor.…”
Section: In Vivo and Organ Distribution Experimentsmentioning
confidence: 95%
“…The blockade experiment with 2-PMPA as a competing ligand led to a significant, but not complete, reduction in tumor uptake. This result might be attributable to the binding mechanism of 2-PMPA, as it has been reported to be a fast and reversible inhibitor (21). Given the high internalization ratio of 18 F-PSMA-1007, only a small fraction of the ligand needs to be bound to be internalized-even in the presence of the competitorand thus might result in significant uptake into the tumor.…”
Section: In Vivo and Organ Distribution Experimentsmentioning
confidence: 95%
“…In addition, the correlation between reversibility of inhibition and GCP II internalization in LNCaP cells has been determined; we found that pseudo-irreversible inhibitors induced internalization to a greater extent than slowly reversible or reversible inhibitors 9 . Furthermore, we recently demonstrated that reversibility of inhibition has an effect on internalization and percent uptake of GCP II-targeted SPECT agents with the irreversible-targeting agent, demonstrating superior uptake and internalization in GCP II-positive (GCP II+) cells 10 .…”
Section: Introductionmentioning
confidence: 89%
“…We previously reported a series of phosphoramidate peptidomimetic inhibitors of PMSA and classified their reversibility of inhibition by monitoring the recovery of enzyme activity following rapid dilution of the enzyme-inhibitor complex 9 . In addition, the correlation between reversibility of inhibition and GCP II internalization in LNCaP cells has been determined; we found that pseudo-irreversible inhibitors induced internalization to a greater extent than slowly reversible or reversible inhibitors 9 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations